Productive education and economic security nexus: lessons for a labour-surplus Nigerian economy (2013)
In Nigeria, as in most other developing countries, the problem of social and economic insecurity has constituted a serious threat to the peace and development of the entire society. This problem is complicated by the daunting challenge of the growing number of unemployed labour force. Although governments at various levels, have been making efforts to improve the economic wellbeing of the citizens through the provision of social Instruments and support by attempting to increase both the individual and societal income, raise opportunity for increased employment as well as reduce the level of poverty in the country, the gap in economic deprivation among the growing population continue to widen. Consequently, there is a high rate of social and economic unrest in the country with its attendant negative effects. Available social-economic indicators revealed that, of the over 92 million economically active population in Nigeria, only 51.2 million (55%) of the labour force were employed in 2010, while the poverty incidence stood at about 70 percent during the some period. The thrust of this paper therefore, was to draw a link between productive education and economic security in the Nigeria labour-surplus economy. The paper concludes that a high quality and market relevant education has the capacity to provide genuine solution to most of the economic problems through the creation and provision of stable employment, increased sources of income for the individual, eradicate poverty and control population growth. It therefore recommends concerted efforts towards developing the nation's educational System as a strategy for improving the economic wellbeing of the citizenry